Genetically modified foods a little safer - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Novartis, a Swiss multinational, has developed a sugar-based replacement for antibiotic resistance marker genes. The latter are used in the development of genetically modified foods, but some scientists fear that these genes might spread to harmful...